Word of Mouth Strategy on Emina Skincare Products - Yuniar, Dinda Fadila; Wandira, Ayu; Nugraha, Nisfa Fathira; Erawati, Dedet (Asian Journal of Social and Humanities, 2025)
The skincare industry is currently experiencing rapid growth, in line with increasing public awareness of the importance of skincare. Every brand implements various marketing strategies to attract consumers, one of which is the Word of Mouth (WOM) strategy. This study examines the phenomenon of the increasing number of skincare products on the market and various research results on the effectiveness of WOM in building consumer loyalty, particularly within beauty communities such as EGGA in Cirebon. Therefore, the objective of this study is to analyze the strategies implemented by Emina in its efforts to acquire, retain, and build relationships with consumers within the EGGA community. The approach used in this study is based on the theory of Integrated Marketing Communication (IMC), which emphasizes the importance of integrated marketing communication in building brand image and customer loyalty. The main indicators analyzed are the contribution of WOM in attracting new consumers (getting), maintaining their loyalty (keeping), and strengthening long-term relationships with customers (building). The research findings indicate that the strategies implemented by Emina in the EGGA Cirebon community are effective in increasing brand awareness, strengthening customer loyalty, and forming an active community of users who share positive experiences. Thus, it can be concluded that WOM is an effective marketing strategy for expanding market reach and increasing consumer engagement in the increasingly competitive skincare industry.